Collaborating for Resilience(CoRe) approach is used to build effective coalitions of civil society and government agencies for pro-poor land governance. - CGIAR Research Program on Policies, Institutions, and Markets (2017)
Collaborating for Resilience(CoRe) approach, provides a structured framework for understanding stakeholder interactions and organizing for social and institutional change. The International Land Coalition is applying this framework to increase the effectiveness of their National Engagement Strategies (NES), which are coalitions of civil society and government agencies for pro-poor land governance. Comparative analysis of experiences using the CoRe framework helps guide decisions on when and how best to engage government in the work of the multi-stakeholder platforms for land tenure reform.